EXPLORING THE EXTENT OF IMPLEMENTATION OF ACTIVITIES BY THE FAS SCHOOLS IN REALIZING TRANSFORMATIVE EDUCATION - LABRADOR FAS, SR. ELLEN (International Journal of Arts, Sciences and Education, 2023)
Among Filipinos, education is considered a weapon against poverty. Also, it is regarded as the best weapon for social mobility. Thus, education is related to the concept of transformation or change. This study aimed to explore the resource capability and extent of implementation of Transformative Education (TE) among Franciscan Apostolic Sisters (FAS) schools. This study employed the descriptive correlational research design. The extent shows that faculty and administrators as respondents on Transformative Education along with justice and peace strongly value a just and peaceful environment. The FAS-owned and administered schools implemented activities along the six pillars of Transformative Education. However, only activities along Justice and Peace were “Fully Implemented”, while activities along ecological security, engaged citizenship, poverty reduction, gender and equality and youth empowerment were “Partially Implemented” as assessed by administrators, teachers and students. As recommended, the FAS administrators should sustain and/or further strengthen the integration of Transformative Education in their curriculum, school philosophy, vision and mission statement and in their governance in order to fully achieve the gains of Transformative education in the behavior of their students and other stakeholders. On one hand, FAS administrators should revisit their weaknesses particularly on human, physical and informational resources because these are critical aspects of building stronger resource capabilities.